Selected Topics in Manufacturing AITeM Young Researcher Award 2021 - Carrino, Luigi; Tolio, Tullio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents selected contributions on a wide range of scientific and technological areas covered by AITeM (the Italian Association of Manufacturing). It discusses the following topics: additive manufacturing, advanced and unconventional machining and processes, material removal processes, foundry and forming, tools and machine tools, assembly/disassembly, joining materials and material properties, quality metrology and material testing, manufacturing systems engineering, sustainable manufacturing, smart manufacturing and cyber-physical systems, education in manufacturing and human factors, industrial applications. Written by young AITeM associates, the contributions reflect the multifaceted nature of the research in manufacturing, which takes advantage of emergent technologies and establishes interdisciplinary connections with various scientific and technological areas to move beyond simple product fabrication and develop a complex and highly interconnected value creation processes ecosystem pursuing high-value-added products to compete globally.
Keywords: Industrial engineering; Production engineering; Manufactures; Materials science; Industrial and Production Engineering; Machines, Tools, Processes; Materials Science; Manufacturing processes